1998
DOI: 10.1111/j.1558-5646.1998.tb05133.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction-Independent Sexual Selection and the Mechanisms of Sexual Selection

Abstract: Darwin identified explicitly two types of sexual selection, male contests (combat and displays) and female choice, and he devoted the overwhelming majority of his examples to traits that influence the outcome of these interactions. Subsequent treatments of sexual selection have emphasized the importance of intra- and intersexual interactions as sources of sexual selection. However, many traits that are important determinants of mating success influence mating success without necessarily affecting the outcome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…Some authors have suggested that the sedentary nature of flowering plants makes the competition for pollinators unlike the competition for mates among animals (e.g., Grant 1995;Murphy 1998). Here, we reinforce that the competition over mates and the competition for pollinator visits can exemplify the same fundamental selection pressure.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Some authors have suggested that the sedentary nature of flowering plants makes the competition for pollinators unlike the competition for mates among animals (e.g., Grant 1995;Murphy 1998). Here, we reinforce that the competition over mates and the competition for pollinator visits can exemplify the same fundamental selection pressure.…”
Section: Discussionsupporting
confidence: 66%
“…For some, the theory encompasses any trait with a positive influence on mating success (e.g. Murphy 1998)-a viewpoint that is particularly apparent in the application of sexual selection theory to flowering plants. Sexual selection in plants is typically defined as selection arising from differences in mating success (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…pollen export and import) relative to conspecifics (cf. interaction-independent sexual selection, Murphy 1998). Sexual selection in plants can also take place after fertilization, when sex-limited expression of traits influence allocation to developing fertilized ovules (Queller 1984).…”
Section: Sexual Selection and Sexual Conflict In Plantsmentioning
confidence: 99%
“…In polygynous mammalian mating strategies, body size is often a key state influencing male-male competitiveness, endurance rivalry, and reproductive success (Andersson 1994;Murphy 1998). In young growing animals, body size increases with age, allowing individuals to become more competitive (Clutton-Brock et al 1979).…”
Section: Introductionmentioning
confidence: 99%